Structural study of copper oxide supported on a ceria-modified titanic catalyst system - Francisco, MSP; Mastelaro, V. R.; Florentino, A. O.; Bazin, D. (Kluwer Academic/plenum Publ, 2002)
A structural study of CuO supported on a CeO2-TiO2 system was undertaken using X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS) techniques. The results of XRD revealed the presence of only two phases, TiO2 anatase and CeO2 cerianite. A trend towards smaller TiO2 crystallites was observed when cerium content increased. When the amount of cerium increased, Ti K-edge XANES analysis showed an increasing distortion of Ti sites. The results of Ce L-III-edge EXAFS showed that Ce atoms are coordinated by eight oxygen atoms at 2.32 Angstrom. For the sample containing a small amount of cerium, the EXAFS analysis indicated that the local structure around Ce atoms was highly distorted. The catalysts presented quite different Cu K-edge XANES spectra compared to the spectra of the CuO and Cu2O reference compounds. The Cu-O mean bond length was close to that of the CuO and the Cu atoms in the catalysts are surrounded by approximately four oxygen atoms in their first shell. Copper supported on the ceria-modified titania support catalysts displayed a better performance in the methanol dehydrogenation when compared to copper supported only on titanic or on ceria.
Keywords: catalysts; CuO-CeO2-TiO2; structure; XRD; XAS